Screening of a Drug Library Identifies Inhibitors of Cell Intoxication by CNF1. (27th February 2018) - Mahtal, Nassim; Brewee, Clémence; Pichard, Sylvain; Visvikis, Orane; Cintrat, Jean‐Christophe; Barbier, Julien; Lemichez, Emmanuel; Gillet, Daniel
Abstract: Cytotoxic necrotizing factor 1 (CNF1) is a toxin produced by pathogenic strains of Escherichia coli responsible for extra‐intestinal infections. CNF1 deamidates Rac1, thereby triggering its permanent activation and worsening inflammatory reactions. Activated Rac1 is prone to proteasomal degradation. There is no targeted therapy against CNF1, despite its clinical relevance. In this work we developed a fluorescent cell‐based immunoassay to screen for inhibitors of CNF1‐induced Rac1 degradation among 1120 mostly approved drugs. Eleven compounds were found to prevent CNF1‐induced Rac1 degradation, and five also showed a protective effect against CNF1‐induced multinucleation. Finally, lasalocid, monensin, bepridil, and amodiaquine protected cells from both diphtheria toxin and CNF1 challenges. These data highlight the potential for drug repurposing to fight several bacterial infections and Rac1‐based diseases. Abstract : Targeting a toxin : Cytotoxic necrotizing factor 1 (CNF1), a bacterial toxin, enhances E. coli virulence. Screening of 1120 mostly approved drugs led to the identification of CNF1 inhibitors by hindering CNF1‐driven multinucleation and Rac1 degradation. This work highlights a new strategy to find virulence factor inhibitors and potential drug repurposing to combat the undesirable effects of CNF1.